2018
DOI: 10.22159/ajpcr.2018.v11i7.21688
|View full text |Cite
|
Sign up to set email alerts
|

Acute Oral Toxicity Study of Ethanolic Extract of Actinoscirpus Grossus (L.F.) Goetgh. And D.A. Simpson

Abstract: Objective: To study the acute oral toxicity of ethanolic extract of Actinoscirpus grossus (L.f.) Goetgh. and D.A. Simpson in Wistar albino rats.Methods: Ethanolic extract of the plant was assessed for single dose acute toxicity by employing Organisation for Economic Co-Operation and Development(OECD) guidelines 425 using Acute Oral Toxicity(AOT) software. The dosed (up or down as per the requirement) rats were observed for 14 days for general appearance, behavior, mortality, and necropsy. A total of 5 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The safety assessments of the FEFLG were performed using OECD guidelines 52 , which are well-accepted worldwide for safety assessments of any chemical that can be exposed or consumed by human beings and are recommended by most regulatory agencies worldwide AOT study determines the exposure ranges and maximum dose at which animal lethality was observed. 75 Female rats are preferred for acute toxicity studies as females are generally sensitive. 76 Results of acute toxicity allow a substance to be ranked and classified according to the GHS for classifying chemicals that cause acute toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety assessments of the FEFLG were performed using OECD guidelines 52 , which are well-accepted worldwide for safety assessments of any chemical that can be exposed or consumed by human beings and are recommended by most regulatory agencies worldwide AOT study determines the exposure ranges and maximum dose at which animal lethality was observed. 75 Female rats are preferred for acute toxicity studies as females are generally sensitive. 76 Results of acute toxicity allow a substance to be ranked and classified according to the GHS for classifying chemicals that cause acute toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…NOAEL is selected after comparing the severity of toxic effects between treated and control groups. 75 The doses for subchronic toxicity of FEFLG (250, 500 and 1000 mg/kg) were selected from the results of AOT to assess safe oral dose levels for long-term human exposure. Repeated oral administration for 90 days of FEFLG did not cause any mortality or toxicity signs at and up to the dose level of 1000 mg/kg body weight during the dosing period and post-dosing recovery period.…”
Section: Discussionmentioning
confidence: 99%